Thermodynamic analysis of a novel integration of a spray dryer and solar collectors: A case study of a milk powder drying system - Camci, Muhammet (TAYLOR & FRANCIS INC, 2020)
This study undertakes a thermodynamic analysis of a spray dryer (SP) integrated with solar collectors. Here, parabolic trough collectors (PTC) and photovoltaic panels are utilized to supply heat and electricity to this integrated system. Such analysis may help to determine the suitability of using solar energy in an environmentally friendly manner in milk powder production. The use of solar energy in milk powder production also provides many opportunities for off-grid rural areas. In the spray drying process, the required hot air, as a drying agent, is heated to around 200 degrees C, which is supplied from focusing the sun on a PTC. As a result of convective evaporation, the milk solution is converted into milk powder in the spray dryer. Before spray drying, milk is concentrated using a vacuum evaporator, which has a higher thermodynamic efficiency than the spray dryer. After setting appropriate inlet parameters (i.e., temperature, pressure, and humidity ratio), the thermodynamic balance equations were solved by Engineering Equation Solver (EES) software, wherein an overall energy efficiency of 75.01% was obtained for milk powder production. The suitability and advantages of using solar energy as a renewable source in spray drying are further discussed.
Keywords: Spray dryer; parabolic trough collector; thermodynamic analysis; milk powder; solar energy; EXERGY ANALYSIS; LIGNITE; AIR; PERFORMANCE; OPERATION; HEAT; Engineering